The Immune Microenvironment in Gastric Cancer: Prognostic Prediction - Ma, Mingwei; Sun, Juan; Liu, Zhen; Ouyang, Siwen; Zhang, Zimu; Zeng, Ziyang; Li, Jie; Kang, Weiming (Frontiers in Oncology, 2022)
Although therapeutic methods have been developed, gastric cancer (GC) still leads to high rates of mortality and morbidity and is the second leading cause of cancer-associated death and the sixth most common cancer worldwide. To understand the factors associated with the prognostic prediction of GC and to discover efficient therapeutic targets, previous studies on tumour pathogenesis have mainly focused on the cancer cells themselves; in recent years, a large number of studies have shown that cancer invasion and metastasis are the results of coevolution between cancer cells and the microenvironment. It seems that studies on the tumour microenvironment could help in prognostic prediction and identify potential targets for treating GC. In this review, we mainly introduce the research progress for prognostic prediction and the immune microenvironment in GC in recent years, focusing on cancer-associated fibroblasts, tumour-associated macrophages (TAMs), and tumour-infiltrating lymphocytes (TILs) in GC, and discuss the possibility of new therapeutic targets for GC.